Problems of French Wine Market Evolution - M. Y. Simonova (Vestnik MGIMO-Universiteta)
France is a leading country in wine producing and exporting. World globalization influences a structure of demand and exports, producers and exporters. Wine makers of France are to change and innovate traditional technologies of production, marketing, sales.